Enhanced Spin-Engineering Photothermoelectric–Enzymatic Catalysis System via Lattice Mismatch-Induced Jahn–Teller Distortion for Tumor Therapy - Zang, Pengyu; Yang, Meiqi; Yu, Chenghao; Zhang, Rui; Sharipov, Avez; Shen, Ruifang; Yang, Dan; Gai, Shili; Yang, Piaoping (Nano-Micro Letters, 2026)
Oxygen-dependent electrodynamic therapy is hindered by electron–hole recombination and hypoxia. This study provides a heterojunction-induced Jahn–Teller distortion-enhanced spin-engineering Fe3O4–Ag2S nanoplatform to address these limitations. The large interfacial lattice mismatch induces previously unrecognized Jahn–Teller distortions on high-spin Fe sites, modifying d-orbital splitting and enhancing spin-polarized catalytic activity. This lattice–spin–carrier coupling synergistically amplifies catalase-, peroxidase-, and glutathioneox-like pathways. Under near-infrared irradiation, the photothermal effect of Fe3O4 activates the thermoelectric response of Ag2S and drives continuous hot-carrier injection. Thermoelectric fields drive hot holes to boost catalase activity through Jahn–Teller effect-enhanced spin catalysis sites and drive hot electrons to convert O2 to cytotoxic O2.− and 1O2 under the Jahn–Teller distortion, promoting and forming a self-amplifying catalytic loop. Fine structure characterization and density functional theory calculations collectively verify strain-driven Fe–O bond differentiation and spin-state reconfiguration. The heterojunction achieves potent thermoelectric–enzyme co-catalysis with 95% tumor inhibition under near-infrared irradiation and supports dual-mode imaging. This work establishes a framework for designing high-performance photothermal–thermoelectric catalysts through crystal field/spin-state modulation in p–n heterojunctions, synergistically boosting multi-enzyme activity and catalytic efficiency for hypoxia-resistant therapy. Highlights: 1 A Fe3O4–Ag2S p–n heterojunction is engineered to induce interfacial Jahn–Teller distortion, which modifies d-orbital splitting and enhances spin-polarized catalytic activity for synergistic tumor therapy. 2 The photothermal-driven thermoelectric effect generates an electric field that facilitates directional charge separation, concurrently boosting multiple enzyme-mimicking activities for enhanced catalytic therapy. 3 Density functional theory calculations confirm that the Jahn–Teller distortion optimizes the d-orbital and spin state of Fe3+, providing a theoretical basis for the superior thermoelectric and enzymatic performance.